The Religious Imagination in Literary Network and Muslim Contestation in Nusantara - Bustamam-Ahmad, Kamaruzzaman (Jurnal Ilmiah Peuradeun, 2019)
This study aims to examine the history of religious imagination and contestation in Nusantara. It will trace the issue of transformation of Islamic thought as religious imagination from Middle East to the region by looking at the network of Muslim scholars, the development of institution, and the distribution of religious ideas in kitabs. I will utilize socio-historical approach as means to understanding the early development of Islamic intellectual. It is said that Aceh as the first place of Islamization process in Nusantara. It can be seen from the early historical facts such as Kingdoms of Peureulak, role of ‘ulama of Pasai, and institution of dayah as place of reproduction of ‘ulama in the region. It is argued that there have been many of anthropological and archaeological evidences that had influenced the early reproduction of Islamic thought in Southeast Asia. In addition, this study will also examine the current potrait of contestation among Muslim in political landscape in the country. It indicates that the identity of Muslim has to do with the roots of historical narrative in the Nusantara.